2018
DOI: 10.1037/fam0000450
|View full text |Cite|
|
Sign up to set email alerts
|

Autonomy support in toddlerhood: Similarities and contrasts between mothers and fathers.

Abstract: Infant exploration often hinges on parental autonomy support (i.e., parental behaviors that support children’s goals, interests, and choices), a construct that is widely applied in family studies of school-age children and adolescents but less studied in infants and toddlers. Notable gaps concern the equivalence, similarities, and contrasts between mothers’ and fathers’ autonomy support and the correlates of individual differences in autonomy support. To address these underresearched topics, we conducted paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…In addition, we found partial measurement invariance (i.e., configural and metric but not intercept invariance) for our latent factor of positive parenting as rated from the interview at each phase of the study. However, while the lack of strict factorial invariance limited our ability to examine changes in positive parenting over time, it should be noted that studies explicitly testing measurement invariance of parenting typically rely upon questionnaire ratings (Widaman, Ferrer, & Conger, 2010), and, consistent with our findings, those who have examined observational ratings have also demonstrated partial measurement invariance (e.g., Hughes, Lindberg, & Devine, 2018). Although the inter-rater reliability of the parental responsiveness scale of the observational measure was low, rather than being unreliable in detecting low parental responsiveness, inspection of the data showed that this was due to ceiling effects in these highly functioning families, as most obtained scores at the top of the scale.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, we found partial measurement invariance (i.e., configural and metric but not intercept invariance) for our latent factor of positive parenting as rated from the interview at each phase of the study. However, while the lack of strict factorial invariance limited our ability to examine changes in positive parenting over time, it should be noted that studies explicitly testing measurement invariance of parenting typically rely upon questionnaire ratings (Widaman, Ferrer, & Conger, 2010), and, consistent with our findings, those who have examined observational ratings have also demonstrated partial measurement invariance (e.g., Hughes, Lindberg, & Devine, 2018). Although the inter-rater reliability of the parental responsiveness scale of the observational measure was low, rather than being unreliable in detecting low parental responsiveness, inspection of the data showed that this was due to ceiling effects in these highly functioning families, as most obtained scores at the top of the scale.…”
Section: Discussionsupporting
confidence: 77%
“…Children further mature in their ability to deliberately engage, both physiologically and socio‐emotionally, in social interactions with both parents during their preschool years (Harrist & Waugh, 2002 ). Concerning the role of child agency in parent–child interactions in that child age range, however, Hughes, Lindberg, and Devine ( 2018 ) showed that mothers’ support for children’s agency and autonomy may be higher than fathers’ support. The potential implication of this finding could be that child agency during father–child interactions in that child age range might not be a driving factor for fathers to engage in a reciprocal interaction with their child (Bureau et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…All participating families ( N = 93) comprised parents aged 20 years or above, spoke English as their primary language, and were cohabiting with a heterosexual partner. The majority of the participating couples (71/93) were recruited from the New Fathers and Mothers Study, a longitudinal study assessing the transition to parenthood in couples in and around Cambridge, United Kingdom (see Hughes, Lindberg, & Devine, 2018). As well as this sample, 17 couples were recruited from a maternity unit of a local hospital, three couples were recruited from a joint database shared by other researchers at the University of Cambridge, and two couples were recruited via word of mouth.…”
Section: Methodsmentioning
confidence: 99%